A two-step simulation methodology for modelling stagnation flame synthesised aggregate nanoparticles - Lindberg, Casper S. (2020)
A two-step simulation methodology is presented that allows a detailed particle model to be used to resolve the complex morphology of aggregate nanoparticles synthesised in a stagnation flame. In the first step, a detailed chemical mechanism is coupled to a one-dimensional stagnation flow model and spherical particle model solved using method of moments with interpolative closure. The resulting gas-phase profile is post-processed with a detailed stochastic population balance model to simulate the evolution of the population of particles, including the evolution of each individual primary particle and their connectivity with other primaries in an aggregate. A thermophoretic correction is introduced to the post-processing step through a simulation volume scaling term to account for thermophoretic transport effects arising due to the steep temperature gradient near the stagnation surface. The methodology is evaluated by applying it to a test case: the synthesis of titanium dioxide from titanium tetraisopropoxide (TTIP) precursor. The thermophoretic correction is shown to improve the fidelity of the post-process to the first fully-coupled simulation, and the methodology is demonstrated to be feasible for simulating the morphology of aggregate nanoparticles formed in a stagnation flame, permitting the simulation of quantities that are directly comparable to experimental observations.